Integrated Model for Destination Revisiting: Elaborating the Effect of Emotional Solidarity & Demographics Including Risk Factors, Social & Political Issue, Crime, Natural Disaster, Health Issues - Anika Nashat Matin, Veer P. Gangwar, Amandeep Kaur (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Intention of the paper is to reveal with elaboration with some imperative influences of destination marketing, derivedfrom gap of multiple research which isassembled within a model to scrutinize its consequencefor revisit intention to a falling trend in a businesssector of Bangladesh ‘tourism’.This study are focused to be more weighted as well as evocative in compiling effect of moderating variable from demographics.Data is collected on self-administered structured questionnaire tool, on 384 on successful completion of gathering data physically from destination, on around 3 months from income generated people of the country. SPSS 26 and AMOS 23havebeen run for data analysis. The showed hypothesis are entirely made for the study from true scenario grounded on the investigations exception made in four. The findings reveal that , the effect of chosen factors of destination marketing as (image of destination, factors of risk and solidarity that comes from emotion) results positively on intention to revisit without any moderation effect of demographics (age, gender, income and education). A positive likelihood association with image of destination along with risk factors towards revisit intention and slight less influence with emotional solidarity where, demographics does not make any link as third variable amongstthe researched variables.The selection of variables of the study are uniquely combined from multiple research gap that pervasive the existing literature gap on tourism industry along with a nimble of assistance ship for involvers of tourism industry of the country that will also make a way out for other tourism industry internationally. Moreover, all types of generations are respondents in the study which results the consequences of demographics as moderation effect more realistic. In order to generalize the study for more time befitting, the study can make towards widespread of destinations of the chosen country along with number of respondents can be more engaging the length of duration long while collecting data.